2016
DOI: 10.1590/1983-084x/15_177
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage time and temperature on the chemical composition of the essential oil of Hyptis pectinata L. Poit

Abstract: ABSTRACT:Hyptis pectinata, popularly known as "sambacaitá", is a native medicinal herb used by local people for treating disease. Its pharmacological, antimicrobial, and medicinal properties have been reported in several studies. The essential oil of the leaves is rich in terpene compounds responsible for its properties. Because there are factors that can influence the chemical composition of essential oils, the objective of this study was to evaluate the influence of storage on Hyptis pectinata essential oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Based on steam distillation, Cassel and Vargas [17] optimized the yield of citronella essential oil extraction. Previous study revealed that microwave assisted hydrodistillation was more efficient in terms of extraction time and energy consumption [18]. There have been many studies attempting oil extraction by hydrodistillation to solve the problem of separation efficiency, composition and utility of essential oils [19].…”
Section: Physico-chemical Characteristics Of Rosmarinus Officinalis Lmentioning
confidence: 99%
“…Based on steam distillation, Cassel and Vargas [17] optimized the yield of citronella essential oil extraction. Previous study revealed that microwave assisted hydrodistillation was more efficient in terms of extraction time and energy consumption [18]. There have been many studies attempting oil extraction by hydrodistillation to solve the problem of separation efficiency, composition and utility of essential oils [19].…”
Section: Physico-chemical Characteristics Of Rosmarinus Officinalis Lmentioning
confidence: 99%
“…In spite of this, the two studies verified the expressive presence of the compound cation of caryophyllene. While in this work the caryophyllene oxide showed the major compound, with its higher concentrations at 55 ° C, in the experiments of Jesus et al (2016) this was the compound with the second highest concentration and remained more stable when stored in a freezer at a temperature of -20 ° C. In this way, we can see the instability of the chemical components in the essential oil when submitted to different temperatures.…”
Section: Resultsmentioning
confidence: 51%
“…Arrigoni-Blank et al (2010) reported that the differences between the chemical compositions can be justified because each genotype responds differently to the given environmental conditions and also to the drying process, which eliminates water from the material and increases the percentage of active principles in comparison with the fresh plant. Jesus et al (2016) also performed the drying of Hyptis pectinata samples, but at a single temperature of 40 ° C for four days, without variations in air drying drier rate. The oil was extracted by steam distillation and stored the samples of oils obtained at temperatures of ±32 ° C and -20 ° C. The objective of the work of Jesus et al (2016) was to evaluate the influence of the time and storage temperature of the oils obtained, and therefore performed chromatographic analyzes in 11 time periods over 360 days, diverging from this work, which aimed to verify the influence of the drying procedures on the chemical composition of Hyptis pectinata essential oil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies reported the composition of the essential oils from Mesosphaerum pectinatum (syn. Hyptis pectinata ) ( Tchoumbougnang et al, 2005 ; Arrigoni-Blank et al, 2008 ; Nascimento et al, 2008 ; Jesus et al, 2016 ; Feitosa-Alcantara et al, 2017 ; Oliveira de Souza et al, 2017 ). These oils presented as the major compounds the sesquiterpene hydrocarbons, β -caryophyllene ( 262 ), germacrene-D ( 269 ) and β -elemene ( 263 ).…”
Section: Phytochemistrymentioning
confidence: 99%